2003
DOI: 10.1021/jm030197g
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis and Optimization of NK1 Receptor Antagonists through Modulation of Atropisomer Interconversion Properties

Abstract: We have previously described a series of antagonists that showed high potency and selectivity for the NK(1) receptor. However, these compounds also had the undesirable property of existing as a mixture of interconverting rotational isomers. Here we show that alteration of the 2-naphthyl substituent can modulate the rate of isomer exchange. Comparisons of the NK(1) receptor affinity for the various conformational forms has facilitated the development of a detailed NK(1) pharmacophore model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…1d/1b, 1b/1a, 1a/1c, and 1c/1d) was not seen. 10 Such behavior has been observed for related naphthamide systems. 11 In these cases, it is understood that the fastest interconversions are due to the simultaneous, paired rotation of the naphthamide -aryl and amide bonds.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…1d/1b, 1b/1a, 1a/1c, and 1c/1d) was not seen. 10 Such behavior has been observed for related naphthamide systems. 11 In these cases, it is understood that the fastest interconversions are due to the simultaneous, paired rotation of the naphthamide -aryl and amide bonds.…”
Section: Introductionsupporting
confidence: 56%
“…13 The long rotational half-life (approximately 1.8 days at 37 8C) allowed us to individually test each component of 1. 10 We found that most of the in vivo NK 1 activity was associated with the single atropisomer, 1d. Using a combination of kinetic and spectroscopic studies, we assigned structures for each of the atropisomers as indicated in Figure 3.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Therefore, historically, equilibration between conformers was rarely considered as impacting nucleation and crystallization kinetics [50]. However, there is steady growing evidence that improved potency of specific conformers under physiological conditions led to an increase in the focus on relatively stable conformers, as evidenced by recent reports [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Since crystallization is the main purification and separation unit operation in the development of new medicines, studies about molecular flexibility and the effect of the presence of conformation stability and conversion in solution on nucleation, crystal growth and polymorphism has also been steadily increasing [50,[69][70][71][72][73][74][75][76][77][78][79][80][81][82].…”
mentioning
confidence: 99%
“…The naphthyl amide organic fragment is prevalent in a number of bioactive compounds [1][2][3][4][5][6] including those targeting the NK1 receptor, 1 the inhibition of aldosterone synthase, 3 the leukocyte proteases cathepsin G 4 and chymase, 5 and a malarial receptor. 2 Aromatic amides including some naphthyl amides are also central to the inhibition of a group of poly(ADP-ribose) polymerase enzymes (PARPs) [7][8][9] that bind NAD + and have been implicated in the cellular response to DNA injury.…”
mentioning
confidence: 99%